REALIZATION OF THE HOLISTIC MARKETING STRATEGY FOR OMNI-CHANNEL RETAIL ON THE EXAMPLE OF THE FOXTROT NETWORK - Filippova, Tetiana; Fisun, Yulia; Borysenko, Olena (Socio-economic relations in the digital society, 2023)
The article examines the main definitions and approaches to holistic marketing by foreign and Ukrainian authors. The business begins to understand that it must shift the emphasis from the product itself and its characteristics to its end consumer, building long-term relations with him - this explains the relevance of this study. Four separate elements of holistic marketing, such as relationship marketing, integrated marketing, socially responsible marketing and internal marketing, are described, and their practical application is considered on the example of the omnichannel Ukrainian retailer of household appliances and electronics "Foxtrot". For a precise and deeper understanding of what a holistic marketing strategy is, three typologically similar definitions have been highlighted and delineated: "concept", "approach" and "strategy". The authors proposed their own definitions of holistic marketing in terms of the above-mentioned terms. In addition, the term "strategy" was highlighted for further consideration of the practical application of holistic marketing on the example of the Foxtrot chain of stores. The practical results of the introduction of complex elements into the network's marketing activities and the implementation of a holistic marketing strategy after the rebranding of "Foxtrot" in 2019 have been demonstrated. It was also considered how Ukrainian business actively began to implement holistic marketing in its activities in the conditions of the Covid-19 quarantine and the beginning of the full-scale invasion of the russian federation into Ukraine.
Keywords: holistic marketing; strategy; integrated marketing; socially responsible marketing; relationship marketing; internal marketing